Elemental Abundance Analyses with DAO Spectrograms - XXVII. The Superficially Normal Stars Theta And (A2 IV), Epsilon Del (B6 III), Epsilon Aqr (A1.5 V), and Iota And (B9 V) - Koçer, Dursun; Adelman, SJ; Çalışkan, H; Gulliver, AF; Tektunalı, HG (EDP SCIENCES S A, 17, AVE DU HOGGAR, PA COURTABOEUF, BP 112, F-91944 LES ULIS CEDEX A, FRANCE, 2003)
The superficially normal stars theta And (A2 V), epsilon Del (B6 III), epsilon Aqr (A1.5 V), and iota And (B9 V), which have rotationally broadened line profiles, are analyzed in a manner consistent with previous studies of this series using 2.4 Angstrom mm(-1) spectrograms obtained with CCD detectors and S/N greater than or equal to 200. Their variable radial velocities strongly suggest they are spectroscopic binaries. As no evidence is seen for lines of their companions they are analyzed as single stars. Their derived abundances are generally near solar. But those for theta And suggest that it is possibly a fast rotating Am star.
Keywords: Stars; A Type Stars; Atomic Transition Probabilities; Singly Ionized Silicon; Oscillator Strengths; Effective Temperatures; Solar Abundance; B-stars; Yıldızlar; Yıldız Tipleri; Atomik Geçiş Olasılıkları; Tek Başına İyonlaşmış Silikon; Osilatör Güçlü; Etkili Sıcaklıklar; Güneş Bolluk; B- yıldızlar